Circular Economy Policies in China and Europe. (4th May 2017) - McDowall, Will; Geng, Yong; Huang, Beijia; Barteková, Eva; Bleischwitz, Raimund; Türkeli, Serdar; Kemp, René; Doménech, Teresa
Summary: The idea of a circular economy (CE) has become prominent in both European and Chinese policy making. Chinese and European perspectives on a CE share a common conceptual basis and exhibit many similar concerns in seeking to enhance resource efficiency. Yet they also differ, and this article explores differences in the focus of CE policy in China and Europe. We present evidence on the differing understandings of the CE concept in Chinese and European policy discourse, drawing on qualitative and quantitative analysis of policy documents, media articles, and academic publications. We show that the Chinese perspective on the CE is broad, incorporating pollution and other issues alongside waste and resource concerns, and it is framed as a response to the environmental challenges created by rapid growth and industrialization. In contrast, Europe's conception of the CE has a narrower environmental scope, focusing more narrowly on waste and resources and opportunities for business. We then examine similarities and differences in the focus of policy activity in the two regions and in the indicators used to measure progress. We show differences in the treatment of issues of scale and place and different priorities across value chains (from design to manufacture, consumption, and waste management). We suggest some reasons for the divergent policy articulation of the CE concept and suggest lessons that each region can learn from the other.